2009
DOI: 10.1007/s00464-008-0315-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of laparoscopic-assisted distal gastrectomy for gastric cancer during a surgeon’s learning curve period

Abstract: Although LADG was more time consuming than ODG, it was a feasible, safe procedure that accomplished the oncological requirements. Postoperative morbidity of LADG was similar to that of ODG, and LADG led to faster postoperative recovery. However, LADG should be performed carefully to prevent unexpected complications, especially during the early learning period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 29 publications
5
41
2
1
Order By: Relevance
“…Several previous reports have suggested that LAG with lymph-node dissection may require at least 50-90 cases for a surgeon to gain competence [25][26][27]. It was reported that complications frequently occur during the introductory period, where the greatest of precaution must be taken [3,28]. In the current study, blood loss was the only parameter that showed a significant difference between the first and last 25 cases.…”
Section: Discussionsupporting
confidence: 43%
“…Several previous reports have suggested that LAG with lymph-node dissection may require at least 50-90 cases for a surgeon to gain competence [25][26][27]. It was reported that complications frequently occur during the introductory period, where the greatest of precaution must be taken [3,28]. In the current study, blood loss was the only parameter that showed a significant difference between the first and last 25 cases.…”
Section: Discussionsupporting
confidence: 43%
“…However, these reports involved only small numbers of cases. When the outcomes of LTG and OTG are compared, the learning curve should also be considered [19,20]. Thus, the experience of the surgeons should be checked before a prospective study, including randomized clinical trials, to minimize bias resulting from operatorassociated factors [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies comparing LADG with ODG in terms of short-term results have been reported from Far Eastern countries, there were few studies that compared LADG with ODG after excluding surgical risk factors which could influence the clinical outcomes [9]. In addition, studies regarding a learning curve effect of LADG are still very limited [10].…”
Section: Introductionmentioning
confidence: 99%